Analysis of Coping Strategy in Overcoming Lack of Food in Coastal Community Households in Lantagi Village, Kulisusu Sub District North Buton District - Arif Rahman; Muhammad Aswar Limi; Samsul Alam Fyka (Department of Agribusiness, Halu Oleo University, 2021)
This study aims to determine Coping Strategy Analysis in Overcoming Deficienciesfood carried out by coastal community households in Lantagi Village, Kulisusu District, North Buton Regency. The research was conducted from January to March 2020 in Lantagi Village, Kulisusu District, North Buton Regency. The population in this study amounted to 175 households and the sample was taken by simple random sampling using the Slovin formula, namely 35 households. Coping Strategy Analysis in Overcoming Deficiencies household food using the Shariff and Khor approach which is divided into two categories, namely strategies related to food and strategies related to income or expenditure. The results showed that households in Lantagi Village, Kulisusu District, North Buton Regencyin The strategy to overcome food shortages related to food, the main strategy to be carried out is to reduce the portion of food and purchasing cheaper foodstuffs (substitution) by 77.1% and strategies related to household income or expenditure the main strategy is a strategy to reduce cigarette consumption by 65.7%.